2023
DOI: 10.1126/sciadv.adf9016
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of influenza-mediated inflammation by immunomodulatory matrix-bound nanovesicles

Raphael J. Crum,
Brydie R. Huckestien,
Gaelen Dwyer
et al.

Abstract: Cytokine storm describes a life-threatening, systemic inflammatory syndrome characterized by elevated levels of proinflammatory cytokines and immune cell hyperactivation associated with multi-organ dysfunction. Matrix-bound nanovesicles (MBV) are a subclass of extracellular vesicle shown to down-regulate proinflammatory immune responses. The objective of this study was to assess the efficacy of MBV in mediating influenza-induced acute respiratory distress syndrome and cytokine storm in a murine model. Intraven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Given the results obtained with this research, demonstrating the rich bioactivity of MBVs, combined with the previously reported unique potential of MBVs for immunomodulatory and regenerative medicine applications, their ability to transfer their bioactive components and the advantage of their nanoscale nature, MBVs represent a promising and novel therapeutic aspect for regenerative medicine [27][28][29][30]. Research regarding the application of other EVs is more advanced and has already led to a number of commercial products and clinical trials for their application, in biomedical fields ranging from drug delivery to gene therapy, tissue regeneration, immunotherapy, cancer therapy, and diagnostics [48,79,80].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Given the results obtained with this research, demonstrating the rich bioactivity of MBVs, combined with the previously reported unique potential of MBVs for immunomodulatory and regenerative medicine applications, their ability to transfer their bioactive components and the advantage of their nanoscale nature, MBVs represent a promising and novel therapeutic aspect for regenerative medicine [27][28][29][30]. Research regarding the application of other EVs is more advanced and has already led to a number of commercial products and clinical trials for their application, in biomedical fields ranging from drug delivery to gene therapy, tissue regeneration, immunotherapy, cancer therapy, and diagnostics [48,79,80].…”
Section: Discussionmentioning
confidence: 59%
“…These contents seem to greatly contribute to the immunomodulatory potential of dECM biomaterials. In different studies, MBVs, even when isolated from different tissue sources, have shown the ability to recapitulate the immunomodulatory and regenerative potential of dECM, and have been successfully used both in vitro and in vivo for different regenerative medicine applications, suggesting their vast potential for biomedical applications [27][28][29][30][31][32][33][34]. Even though MBVs seem to be a ubiquitous component of the ECM, maintained even after the tissue decellularisation process, to date, they have only been isolated from small intestine submucosa, urinary bladder matrix, dermis, brain, oesophagus, heart, muscle, liver, ovary, pancreas, and tendons [23][24][25]35].…”
Section: Introductionmentioning
confidence: 99%